PEMBELAAN TERPAKSA (NOODWER EXCES) TERHADAP PELAKU TINDAK PIDANA ANAK YANG MENGAKIBATKAN MATINYA ORANG LAIN - Via Varacika (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
ABSTRACT Self-defense is one of the rights and obligations are given by law to every person to maintain the safety of his life, both the safety of his life, property, and honor. that basically self-defense is a right which is instinctual for every person to defend himself or others, his property and honor from the evil deeds of other parties, which want to damage or harm illegally.An act that qualifies as a criminal offense for children is an act in the form of a crime or a violation as regulated in the criminal law legislation.For the application of the provisions of Article 49 of the Criminal Code, the following elements must be met: There is an attack that is instantaneous or threatens directly; The attack was against the law; The attack is against oneself or others, the honor of decency or the property of one's own or others.Law enforcement officers, especially the judges, apply the rules of article 49 of the Criminal Code. because these rules are legal protection against harm and other crimes against someone. Keywords: Forced Defense, Child Crime